Engineering Mechanics: Statics, 4th Edition - Andrew Pytel; Jaan Kiusalaas (Cengage Learning, 2016)
ENGINEERING MECHANICS: STATICS, 4E, written by authors Andrew Pytel and Jaan Kiusalaas, provides readers with a solid understanding of statics without the overload of extraneous detail. The authors use their extensive teaching experience and first-hand knowledge to deliver a presentation that's ideally suited to the skills of today's learners. This edition clearly introduces critical concepts using features that connect real problems and examples with the fundamentals of engineering mechanics. Readers learn how to effectively analyze problems before substituting numbers into formulas -- a skill that will benefit them tremendously as they encounter real problems that do not always fit into standard formulas. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.